2007
DOI: 10.1093/beheco/arm030
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment in live-bearing fishes (Poeciliidae): comparing courting and noncourting species

Abstract: Sexual harassment by males has been reported from several live-bearing fishes (Poeciliidae) and has been shown to inflict costs on females. For example, poeciliid females have reduced feeding opportunities when accompanied by a male because females dedicate attention to avoiding male copulation attempts. Poeciliid species differ considerably in male mating behavior, such as the presence or absence of courtship. Courting males display in front of the females, but males attempting to sneak-copulate approach fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 86 publications
(94 reference statements)
4
78
0
Order By: Relevance
“…Poeciliid males tend to switch frequently between shoals (Magurran 1998;Griffiths and Magurran 1998) and show more investigative behavior (Andreev 1994), which may come along with a generally higher activity metabolic rate. Even though sexual activity is reduced in the cave population of P. mexicana, probably as an adaptation to save energy (Plath et al 2003(Plath et al , 2007aPlath 2008), males still devote more time and energy to finding mates than females.…”
Section: Discussionmentioning
confidence: 99%
“…Poeciliid males tend to switch frequently between shoals (Magurran 1998;Griffiths and Magurran 1998) and show more investigative behavior (Andreev 1994), which may come along with a generally higher activity metabolic rate. Even though sexual activity is reduced in the cave population of P. mexicana, probably as an adaptation to save energy (Plath et al 2003(Plath et al , 2007aPlath 2008), males still devote more time and energy to finding mates than females.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mate-sampling females may be injured in aggressive courtship displays by males or even suffer from harassment by males (Schlupp et al 2001). Plath et al (2007) performed a comparative approach with nine species of livebearing fish and examined costs of male sexual harassment for females as reduced feeding time. In all species females spent significantly less time feeding in the presence of a male.…”
Section: Benefits Of Eavesdroppingmentioning
confidence: 99%
“…In some species, courting males behave aggressively towards females, or even harass females, during courtship displays (Schlupp et al 2001;Ojanguren & Magurran 2007;Plath et al 2007). A female that observes how a male courts another female gains information about this male, and may reject an aggressive male, without being physically involved (Witte & Ueding 2003).…”
Section: Benefits Of Mate-choice Copyingmentioning
confidence: 99%
“…Several studies have reported on costs for females arising from this male sexual harassment in terms of a reduction of female feeding efficiency in the presence of a harassing male (guppy, P. reticulata: Magurran and Seghers 1994a;Griffiths 1996;mosquitofish, Gambusia holbrooki: Pilastro et al 2003; sailfin molly, P. latipinna: Schlupp et al 2001;surface-dwelling P. mexicana: Plath et al 2003asurface-dwelling P. mexicana: Plath et al , 2007b. A notable exception is the cave molly: as a consequence of the decreased sexual activity of the males, sexual harassment is basically absent in this population (Plath et al 2003a(Plath et al , 2004a(Plath et al , 2007b. Hence, another question of the current study was to investigate if both surface-and cave-dwelling (nonreceptive) P. mexicana females would avoid males and prefer to associate with another female.…”
Section: Introductionmentioning
confidence: 94%
“…For example, cave mollies exhibit reduced shoaling (Parzefall 1993b), aggressive behavior (Parzefall 1974(Parzefall , 1979 and male sexual activity (Plath et al 2003a(Plath et al , 2005a(Plath et al , 2007b. These reductions have traditionally been interpreted as consequences to life in darkness (Parzefall 2001), but the roles of energy limitation and the presence of H 2 S have not been fully considered yet (for discussions see Tobler et al 2006;Plath et al 2007a, c).…”
Section: Introductionmentioning
confidence: 99%